2011
DOI: 10.1044/0161-1461(2010/10-0052)
|View full text |Cite
|
Sign up to set email alerts
|

Creative and Stylistic Devices Employed by Children During a Storybook Narrative Task: A Cross-Cultural Study

Abstract: Purpose The purpose of this study was to analyze the effects of culture on the creative and stylistic features children employ when producing narratives based on wordless picture books. Method Participants included 60 first- and second-grade African American, Latino American, and Caucasian children. A subset of narratives based on wordless picture books collected as part of a larger study was coded and analyzed for the following creative and stylistic conventions: organizational style (topic centered, linear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
51
2
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(65 citation statements)
references
References 52 publications
6
51
2
4
Order By: Relevance
“…Our findings are similar to those reported by deVilliers (2004), Celinska (2009) and Gorman et al, (2012) who elicited narratives from children using a modeled context to minimize potential cultural differences that may impact narrative feature use. Using a modeled elicitation context it is reasonable to expect similar microstructure and macrostructure elements to be present in the narratives of AA and EA children, with the exception of Plan.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Our findings are similar to those reported by deVilliers (2004), Celinska (2009) and Gorman et al, (2012) who elicited narratives from children using a modeled context to minimize potential cultural differences that may impact narrative feature use. Using a modeled elicitation context it is reasonable to expect similar microstructure and macrostructure elements to be present in the narratives of AA and EA children, with the exception of Plan.…”
Section: Discussionsupporting
confidence: 80%
“…It is well-known that the provision of a model decreases the likelihood of bias in assessment for culturally and linguistically diverse populations (Laing & Kamhi, 2003;Lidz & Pena, 1996). This study and others have shown that a modeled narrative elicitation context yields similar stories that contain similar macrostructural and microstructural elements for AA and EA children regardless of the age level sampled (Gorman et al, 2012). However, our findings suggest there may be even less cultural variation in microstructure making it a better "indicator" of narrative "integrity" than macrostructure, which may be more susceptible to the influence of cultural schema or knowledge (Curenton & Justice, 2004).…”
Section: Clinical Implications/summarycontrasting
confidence: 53%
See 1 more Smart Citation
“…Chen and Pan, 2009) • linguistic and cognitive abilities of children from different language and /or cultural back grounds (since most of these are conducted in the US they usually concern either Spanish, Chinese or African American children) (e.g. Gorman et al, 2011) • home/family literacy research and intervention (e.g. Caspe, 2009) • creative writing (e.g.…”
Section: Research Studies From 1998 -2012mentioning
confidence: 99%
“…Therefore, stories from children who are growing up in different cultures may differ and may require assessment that is culturally sensitive. Although some recent work has focused on narrative development in children with Hispanic and African American (AA) backgrounds (Champion, 2003;Fiestas & Peña, 2004;Gorman, Fiestas, Pena, & Clark, 2011;Gutierrez-Clellen & Quinn, 1993), most developmental research on narratives has been conducted on populations from European American (EA) backgrounds (Gee, 1986;Hester, 1996). Best practices have not yet been established for assessing narratives from a broader range of children, including AAs (Champion, 2003).…”
mentioning
confidence: 99%